Muza w kościele. Poetycka gratulacja Franciszka Dionizego Kniaźnina z okazji konsekracji Księdza Adama Stanisława Naruszewicza Biskupa Koadiutora Smoleńskiego - Pawlata, Małgorzata (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
The Ode written by Franciszek Dionizy Kniaźnin is the last one in the series of six odes entitled For the occasion of consecration of priest Adam Stanisław Naruszewicz, the Archbishop coadjutor of Smoleńsk (Z okoliczności tejże [konsekracji Ks(iędza) A(dama) S(tanisława) Naruszewicza B(iskupa) K(oadiutora) S(moleńskiego)]. The odes were published in 1775 in the magazine ‘Pleasant and useful games’ („Zabawy Przyjemne i Pożyteczne”). They are a poetic account of a celebration held on 25th or 28th May 1775 in St. John’s collegiate church in Warsaw and at the same time panegyric praising merita of the poet Bishop. The work is very interesting especially as a documentary as it lists names of guests that gathered for the celebrations, one of which was the king Stanisław August Poniatowski. It also shows relationships among the elite of the capital city at the time. It is worth noting that the way of illustrating is typical for Kniaźnin in a sense and introduces mythological elements in the description of religious celebration.